Compliance deconstructed. - Cannon, J.C. (New York ACM, 2006)
When you break it down, compliance is largely about ensuring that business processes are exectuted as expected.
Keywords: Software; Software engineering; Software/program verification; Validation; Computing Milieux; Management of Computing and Information Systems; Project and people management; Software management; System management